Cell migration is negatively modulated by ABCA1. Issue 3 (4th March 2019) - Ito, Shiho; Kioka, Noriyuki; Ueda, Kazumitsu
ABSTRACT: Temporal and spatial changes of membrane lipid distribution in the plasma membrane are thought to be important for various cellular functions. ATP-Binding Cassette A1 (ABCA1) is a key lipid transporter for the generation of high density lipoprotein. Recently, we reported that ABCA1 maintains an asymmetric distribution of cholesterol in the plasma membrane. Here we report that ABCA1 suppresses cell migration by modulating signal pathways. ABCA1 knockdown in mouse embryonic fibroblasts accelerated cell migration and increased activation of Rac1 and its localization to detergent-resistant membranes. Phosphorylation of MEK and ERK also increased. Inhibition of Rac1 or MEK-ERK signals suppressed cell migration in ABCA1 knockdown cells. Because our experimental conditions for cell migration did not contain cholesterol or lipid acceptors for ABCA1, cellular cholesterol content was not changed. These data suggest that ABCA1 modulates cell migration via Rac1 and MEK-ERK signaling by altering lipid distribution in the plasma membrane. Graphical abstract: : ABCA1 does not only eliminates excess cholesterol via HDL generation, but modulates cell migration by changing lipid distribution within the membrane.